The effects of the eurosystem's APP on euro area bank lending: Letting different data speak - Barno A. Blaes; Björn Kraaz; Christian J. Offermanns (Deutsche Bundesbank, 2019)
We study the implications of the Eurosystem's expanded Asset Purchase Programme (APP) for the bank lending business of euro area banks with euro area non-financial corporations (NFCs) using microeconometric matching techniques. Based on confidential bank-level data on quantitative balance sheet items and interest rates as well as on qualitative survey responses to the Eurosystem's Bank Lending Survey, we identify the exposure of banks to the APP and corresponding effects on loan growth. We find that the APP was effective in stimulating the lending activity with NFCs for a subset of relatively sound banks. At the same time, our results show that there is a non-negligible number of banks with less healthy balance sheets which could not transfer the APP stimulus into more lending. Instead, such banks appear to have used the APP stimulus for consolidating their balance sheets, thereby also reducing their lending business with NFCs. This confirms the importance of accounting for the large degree of heterogeneity in the euro area banking sector in analyses of the effectiveness of monetary policy measures.
Keywords: E52; G21; C21; 330; lending to non-financial corporations; bank-level data; bank heterogeneity; unconventional monetary policy; treatment effects; regression-adjusted matching